EFFECT OF SOLVENT TYPE ON THE AMOUNT OF YIELD FROM MACERATION OF MORINGA PLANTS (Moringa oleifera) - Wulan Anggestia; Sri Pandu Utami; Darmawangsa; Widya P Sari; Difa Dirgantara (Fakultas Kedokteran Gigi, Universitas Mahasaraswati Denpasar, 2024)
Introduction: The use of herbal plants in the field of dentistry has begun to be widely studied, but it is still not widely developed. One of the uses of herbal plants is to make them as raw materials for Moringauthwash. The Moringa plant (Moringa oleifera/Moringa) is an herbal ingredient that qualifies as an alternative antibacterial agent. The type of solvent, extraction temperature, and extraction duration are some variables that can affect the extraction yield, but the dominant type of solvent for the extraction of herbal plants, especially Moringa, is still not specific.This study aimed to determine the effect of solvent types on the amount of yield of the maceration of Moringa plants. Method: This was a true experimental study using a factorial complete randomized design with maceration (method of extraction) on Moringa oleifera with variations in solvent types. Results: The Kruskall-Wallis test showed that based on the solvent type treatment group, a significant value of 0.003 (<0.05) was obtained, meaning that there was an influence of the type of solvent on the amount of yield from Moringa oleifera maceration. Conclusion: In conclusion, the type of solvent has a significant effect on the amount of yield resulting from Moringa maceration.